Seismic Motion, Lithospheric Structures, Earthquake and Volcanic Sources: The Keiiti Aki Volume - Ben-Zion, Yehuda (Pageoph Topical Volumes, 2003)
Geophysicists use seismic signals to image structures in the Earth's interior, to understand the mechanics of earthquake and volcanic sources, and to estimate their associated hazards. Keiiti Aki developed pioneering quantitative methods for extracting useful information from various portions of observed seismograms and applied these methods to many problems in the above fields. This volume honors Aki's contributions with review papers and results from recent applications by his former students and scientific associates pertaining to topics spawned by his work. Discussed subjects include analytical and numerical techniques for calculating dynamic rupture and radiated seismic waves, stochastic models used in engineering seismology, earthquake and volcanic source processes, seismic tomography, properties of lithospheric structures, analysis of scattered waves, and more. The volume will be useful to students and professional geophysicists alike